2021
DOI: 10.3389/fncom.2021.565244
|View full text |Cite
|
Sign up to set email alerts
|

EEGs Vary Less Between Lab and Home Locations Than They Do Between People

Abstract: Given the rapid development of light weight EEG devices which we have witnessed the past decade, it is reasonable to ask to which extent neuroscience could now be taken outside the lab. In this study, we have designed an EEG paradigm well suited for deployment “in the wild.” The paradigm is tested in repeated recordings on 20 subjects, on eight different occasions (4 in the laboratory, 4 in the subject's own home). By calculating the inter subject, intra subject and inter location variance, we find that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…An additional benefit of our use of mobile EEG devices [ 69 ] over laboratory PSG is the ease of protocol adherence and ecological validity, as participants can record EEG in their homes. While laboratory recordings are often affected by first night effects [ 70 ], recent research has shown that there is relatively little difference between EEG recordings undertaken in the laboratory or at home [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…An additional benefit of our use of mobile EEG devices [ 69 ] over laboratory PSG is the ease of protocol adherence and ecological validity, as participants can record EEG in their homes. While laboratory recordings are often affected by first night effects [ 70 ], recent research has shown that there is relatively little difference between EEG recordings undertaken in the laboratory or at home [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the most advanced methods are based on dry-contact electrodes embedded on individualized earpieces made of soft silicone (Kappel et al, 2018). The first ear-EEG sleep assessment study was performed in 2019 (Mikkelsen et al, 2019(Mikkelsen et al, , 2021bTabar et al, 2020Tabar et al, , 2021 using custom made earplugs and a commercial amplifier. In the current study we deployed a recent advancement in the development of a comfortable, generic, and ready to use setup for sleep assessment, without the sacrifice of performance.…”
Section: Introductionmentioning
confidence: 99%
“…This is thanks to non-invasive, portable, and reliable devices such as functional near-infrared spectroscopy (fNIRS) and electroencephalography (EEG). They offer a signal quality while recording in the field that is comparable with that of a fully-controlled lab environment ( 21 23 ). This is an emerging field of research that offers an opportunity to identify the specific pathways between therapeutic effects of nature on mental health and individual differences in brain pattern activity in the general and clinical populations.…”
Section: Introductionmentioning
confidence: 99%